Milk consumption, dietary calcium intake and nutrient patterns from adolescence to early adulthood and its effect on bone mass: the 1993 Pelotas (Brazil) birth cohort - Isabel Oliveira Bierhals; Juliana dos Santos Vaz; Ana Maria Baptista Menezes; Fernando César Wehrmeister; Leonardo Pozza; Maria Cecília Formoso Assunção
The objective of this study is to evaluate the effect of milk consumption, dietary calcium intake and nutrient patterns (bone-friendly and unfriendly patterns) from late adolescence to early adulthood, on bone at 22 years of age. Cross-sectional analysis was performed with 3,109 participants from 1993 Pelotas (Brazil) birth cohort in the follow-ups of 18 and 22 years of age. Bone mineral density (BMD) of the lumbar spine, right femur and whole body were assessed at 22 years using a dual-energy X-ray absorptiometry (DXA). The exposure variables (dietary calcium, milk and nutrient patterns) were created by combining the consumption frequencies between the two follow-ups (always low, moderate, high, increase or decrease). Multiple linear regressions were performed, stratified by sex. In the right femur site, men classified into the "always high" (mean = 1.148g/cm²; 95%CI: 1.116; 1.181) and "increased" categories of milk consumption (mean = 1.154g/cm²; 95%CI: 1.135; 1.174) presented a slightly low BMD comparing with low (mean = 1.190g/cm²; 95%CI: 1.165; 1.215) and moderate (mean = 1.191g/cm²; 95%CI: 1.171; 1.210) categories. In addition, men always classified in the highest tertile of the "bone-unfriendly" pattern presented the lowest mean of whole body BMD (mean = 1.25g/cm²; 95%CI: 1.243; 1.266). No associations were observed between the categories of dietary calcium intake and "bone-friendly" pattern and each of the three BMD outcomes. These results point to the fact that diets composed of inhibiting foods/nutrients can contribute negatively to bone health.